2017
DOI: 10.1189/jlb.3ru0317-090rr
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of cyclophilin A in regulating cytokine secretion

Abstract: Cyclophilin A (CypA), a peptidylprolyl - isomerase, is a ubiquitous and multifunctional protein. In addition to its role as a host-cell receptor for cyclosporine A, CypA has diverse functions in inflammatory conditions and diseases. CypA secreted in response to inflammatory stimuli binds to the cell surface via its receptor CD147 and induces secretion of various inflammatory cytokines. However, silencing and inhibition of either CypA or CD147 inhibits inflammatory cytokine expression and inflammation. This rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 60 publications
0
54
0
1
Order By: Relevance
“…13 CD147 is also presented in activated inflammatory cells and participates the regulation of cytokine secretion and leukocytes chemotaxis by binding with cyclophilin A (CyPA). 14,15 CyPA is a proinflammatory cytokine that is up-regulated in response to virus infection. 16 Our previous studies demonstrated that antibody targeting CD147 inhibited CyPA-induced T cell chemotaxis thus attenuating the local inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…13 CD147 is also presented in activated inflammatory cells and participates the regulation of cytokine secretion and leukocytes chemotaxis by binding with cyclophilin A (CyPA). 14,15 CyPA is a proinflammatory cytokine that is up-regulated in response to virus infection. 16 Our previous studies demonstrated that antibody targeting CD147 inhibited CyPA-induced T cell chemotaxis thus attenuating the local inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…CypA is a member of the cyclophilin family proteins that have peptidyl‐prolyl isomerase activity and are thought to play an important role in protein folding . Meanwhile, CypA is a pro‐inflammatory regulator that could regulate various immunity reaction with pathogen invasion . To verify the interaction between PknG and CypA, we used BLI, finding that PknG indeed strongly binds to CypA (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…[33] Meanwhile, CypA is a pro-inflammatory regulator that could regulate various immunity reaction with pathogen invasion. [34] To verify the interaction between PknG and CypA, we used BLI, finding that PknG indeed strongly binds to CypA (Figure 4A). We also verified this interaction in vivo by co-IP, PknG was overexpressed in 293T cells.…”
Section: Cypa Is a Substrate Of Pkngmentioning
confidence: 99%
“…Cyclophilin A (CyA), an 18 kDa peptidylprolyl cis-trans isomerase, is a ubiquitous and multifunctional protein. In addition to its role as a host-cell receptor for cyclosporine A, CyA has diverse functions in inflammatory conditions and diseases [15,16]. The 52-kDa FK506-binding protein (FKBP52) an immunophilin belonging to the FKBP family, is a known co-chaperone of the heat shock protein 90 (HSP90) and thus may play a role in the intracellular trafficking of hetero-oligomeric forms of the steroid hormone receptors [17,18].…”
Section: Introductionmentioning
confidence: 99%